Analisis Kinerja Aparatur Sipil Negara (ASN) Kecamatan Dalam Pelayanan Publik di Kecamatan Sibolangit Kabupaten Deli Serdang - Sastra, Sastra; Ritonga, Syahfruddin; Lubis, Khairunnisah (Universitas Medan Area, 2024)
This study focuses on evaluating the performance of the State Civil Apparatus (ASN) in Sibolangit District, Deli Serdang Regency, especially in the context of public services. Using a qualitative approach with interviews, observation, and document analysis techniques, this study aims to describe the quality of ASN performance in the region and offer recommendations for improvement. ASN background education affects the allocation of tasks, where low educational qualifications are often an obstacle. Initiative and time management also affect their performance. Effective leadership and good communication are important factors in improving the quality of work. Challenges such as inadequate education and insufficient infrastructure must be addressed. Training and workshops are identified as solutions to improve the knowledge and skills of civil servants. Effective communication between officials and leaders is also emphasized. To improve the quality of work, active participation in training and support from leaders is needed.